Current Approach to Planning Angiography and MAA Administration - Commander, Clayton W.; Mauro, David M. (Seminars in Interventional Radiology, 2021)
Transarterial radioembolization of primary and secondary hepatic malignancies utilizing yttrium-90 microspheres is a commonly performed treatment by interventional radiologists. Traditionally performed as a two-part procedure, a diagnostic angiography is performed 1 to 3 weeks prior to treatment with the injection of technetium-99m-macroaggregated albumin followed by planar scintigraphy in the nuclear medicine department. Careful attention must be paid to the details during the diagnostic angiography to ensure the delivery of a safe and optimal dose to the diseased liver and to minimize radiation-induced damage to both unaffected liver and adjacent structures. In this article, we will review the steps and considerations that must be made during the angiography planning and discuss current and future areas of research.
Keywords: yttrium-90; radioembolization; liver cancer; diagnostic angiography; interventional radiology